'Doing' kinship: heterosexual parents' experiences of non-genetic parenthood through donor conception. Issue 1 (January 2023) - Siermann, Maria; Visser, Marja; Schrijvers, Anne; Mochtar, Monique; Gerrits, Trudie
Abstract: Research question: How do Dutch heterosexual parents who achieved parenthood through donor conception navigate non-genetic parenthood and kinship? Design: A qualitative in-depth semi-structured interview study was performed between September 2018 and January 2019 with both partners of 13 Dutch heterosexual couples where the male partner suffered from infertility and who conceived a child with the help of a sperm donor. Interview questions were based on literature and clinical experiences of experts in the field of donor conception. Interviews were transcribed and analysed using thematic analysis. Results: All parents navigated non-genetic parenthood through 'doing' kinship: they negotiated the importance of nature versus nurture with regards to donor conception and non-genetic parenthood. Most parents perceived genetics as irrelevant for experiencing parenthood, bonding with their children and the preferred role of the donor in their future lives. Yet most of them found genetics relevant for generating similarities between the father and the child, and for wanting the same donor for all their children to ensure a full genetic relation among them. Additionally, based on the donor's genetic bond with the child, some men were anxious about the donor's role in the child's future life and the consequences for their position as a non-genetic father. A few women perceived genetics as relevant in terms of possible inherited illnesses from the donor. Conclusions: Parents experienced several ambiguities regarding the role of genetics in donor conception and navigated 'doing' kinship in various ways. These aspects need to be taken into consideration during the counselling of prospective parents planning to conceive with donor conception.